A framework for cooperation behavior of start-ups: Developing a multi-item scale and its performance impacts. Issue 6 (9th December 2019) - Garidis, Konstantin; Rossmann, Alexander
Abstract : Purpose: Many start-ups are in search of cooperation partners to develop their innovative business models. In response, incumbent firms are introducing increasingly more cooperation systems to engage with start-ups. However, many of these cooperations end in failure. Although qualitative studies on cooperation models have tried to improve the effectiveness of incumbent start-up strategies, only a few have empirically examined start-up cooperation behavior. The paper aims to discuss these issues. Design/methodology/approach: Drawing from a series of qualitative and quantitative studies. The scale dimensions are identified on an interview based qualitative study. Following workshops and questionnaire-based studies identify factors and rank them. These ranked factors are then used to build a measurement scale that is integrated in a standardized online questionnaire addressing start-ups. The gathered data are then analyzed using PLS-SEM. Findings: The research was able to build a multi-item scale for start-ups cooperation behavior. This scale can be used in future research. The paper also provides a causal analysis on the impact of cooperation behavior on start-up performance. The research finds, that the found dimensions are suitable for measuring cooperation behavior. It also shows a minor positive effect on start-up's performance. Originality/value: The research fills the gap of lacking empirical research on the cooperation between start-ups and established firms. Also, most past studies focus on organizational structures and their performance when addressing these cooperations. Although past studies identified the start-ups behavior as a relevant factor, no empirical research has been conducted on the topic yet.